DEMYSTIFYING DEMAND MANAGEMENT TO ENHANCE SUPPLY CHAIN MANAGEMENT PERFORMANCE IN THE SOUTH AFRICAN PUBLIC SECTOR - Vyas-Doorgapersad, Shikha; Zitha, H (Journal of Economic Development, Environment and People, 2024)
One of the phenomena brought about by the genesis of supply chain management (SCM) in the South African public procurement sector arena is demand management (DM). If properly implemented, departments may be able to plan their procurement activities and has the potential to convert a procurement office from a mere reactive function into a fit for purpose office which will be responsive to the needs of its stakeholders in a more efficient and effective manner. Despite its glorious intensions, many government departments are still grappling with the implementation of DM function. The guiding question is: what are the obstacles preventing demand management functions from being implemented successfully? To find answers, the study applies a qualitative research approach, and information is obtained from literature review. Conceptual analysis is considered to analyse the data. The study aims to demystify the concept and provide a practitioner’s perspective regarding the implementation of DM. The motivation of the study is that the findings may assist procurement officials on how to implement DM effectively serving the needs of SCM. It may also serve as springboard in the body of knowledge, thus being used as a point of reference and continue to illuminate public discourse in the public sector procurement environment.